2019
DOI: 10.1002/osp4.390
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐effectiveness of pharmacotherapy and lifestyle intervention in the treatment of obesity

Abstract: Background: The Food and Drug Administration has approved several pharmacotherapies for the treatment of obesity. This study assesses the cost-effectiveness of six pharmacotherapies and lifestyle intervention for people with mild obesity (body mass indices [BMIs] 30 to 35). Methods: A microsimulation model was constructed to compare seven weight loss strategies plus no treatment: intensive lifestyle intervention, orlistat, phentermine, phentermine/topiramate, lorcaserin, liraglutide, and semaglutide. Weight lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 43 publications
2
33
0
1
Order By: Relevance
“…Currently, very few weight-loss drugs have been approved for use by the FDA, other than Lorcaserin and Orlistat, which have relatively modest clinical efficacy and have not been widely used in clinical practice or well known to the public (24). Additionally, phentermine is not the best choice for cardiovascular disease patients because of its adverse effects even if it has a better curative effect (25).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, very few weight-loss drugs have been approved for use by the FDA, other than Lorcaserin and Orlistat, which have relatively modest clinical efficacy and have not been widely used in clinical practice or well known to the public (24). Additionally, phentermine is not the best choice for cardiovascular disease patients because of its adverse effects even if it has a better curative effect (25).…”
Section: Discussionmentioning
confidence: 99%
“…Only 2.4 and 2.2% of participants receiving continued semaglutide and placebo, respectively, discontinued treatment because of adverse events with one death reported in each group attesting to the safety of maintenance therapy. Lee et al [26 ▪ ] assessed cost-effectiveness of pharmacotherapy and lifestyle intervention in the treatment of obesity and reported that semaglutide was the most effective strategy in the 3-and 5-year time horizons, with total quality-adjusted life years (QALYs) of 2.224 and 3.711, respectively but, the incremental cost-effectiveness ratios were prohibitively high at $1437 340/QALY after 3 years and $576931/QALY after 5 years its high price. If semaglutide is made more affordable, this effective therapy will be available to more individuals with obesity and can be cost effective.…”
Section: Discussionmentioning
confidence: 99%
“… 58 However, for the treatment of obesity, semaglutide was found to be not as cost-effective as other obesity pharmacotherapy due to its relatively higher costs, despite its more significant clinical impact than other drug therapies for obesity. 59 Of note, the abovementioned studies do not include evidence from recently published STEP studies. Further cost-effectiveness studies of semaglutide in people with obesity will be supported by the ongoing SELECT (Semaglutide effects on heart disease and stroke in patients with overweight or obesity; ClinicalTrials.gov identifier: NCT03574597) study investigating major adverse cardiovascular outcomes in people who were overweight or obese without T2D.…”
Section: Cost-effectiveness Of Glp-1ras In Obesitymentioning
confidence: 99%